Meeting God in the other: studies in religious encounter and pluralism in honour of Dorin Oancea on the occasion of his 70th birthday - Pătru, Alina (Orientalia - patristica - oecumenica, 2019)
"The present volume unites 44 studies to honor Prof. Dr. Dorin Oancea, Romanian-Orthodox theologian and religious studies scholar, well known as a bridge-builder between Eastern and Western Christian Traditions. The manifold studies reflect upon the fundaments of interfaith and inter-confessional openness, offer insightful examples from past and present, or point to the loci where this openness can and should be achieved today. A meaningful collection for all those interested in present day ecumenical theology, in inter-confessional studies or theology of religions."--Provided by publisher, back cover